La politique de l’Art au musée national de Katmandou (Népal) - Élise Fong-Sintès (Ateliers d'Anthropologie)
Since the 19th century, the National Museum of Kathmandu has been used by the Nepalese government to promote a coherent vision of the nation, its history and its art. In this place, art, which has become national, assumes a political character as the medium of a homogeneous and prestigious image of Nepal. Nevertheless, the two art galleries in which it is exhibited offer paradoxical discourses on “Nepalese art”: one raises the art of the Kathmandu Valley to the rank of national art; the other, based on a Buddhist history of Nepal, broadens this category to works from all over the national territory. This article will show that this paradox is in fact characteristic of a particular trait in Nepal that consists in never completely erasing the past. Through this museum, structured as a conglomeration of different national discourses, the problematic history of defining a “Nepalese art” and constructing a museum representation of Nepal will be apprehended.